2006
DOI: 10.1152/ajprenal.00414.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis induces changes in the expression and distribution of Toll-like receptor 4 in the rat kidney

Abstract: like receptors (TLRs) are now recognized as the major receptors for microbial pathogens on cells of the innate immune system. Recently, TLRs were also identified in many organs including the kidney. However, the cellular distribution and role of these renal TLRs remain largely unknown. In this paper, we investigated the expression of TLR4 in a cecal ligation and puncture (CLP) model of sepsis in Sprague-Dawley rats utilizing fluorescence microscopy. In sham animals, TLR4 was expressed predominantly in Tamm-Hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
147
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(154 citation statements)
references
References 53 publications
7
147
0
Order By: Relevance
“…23 A further report demonstrated that podocytes express a range of chemokines in response to TLR4 stimulation. 21 However, TLR4 has been localized to the glomerular endothelium rather than podocytes in frozen rat kidney, 24 and it seems likely that the findings would be the same in mice. Both Myd88 and TRIF dependent TLR4 signaling has been shown in murine mesangial cells, although TRIF deficient mice developed nephrotoxic nephritis to a similar degree to wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…23 A further report demonstrated that podocytes express a range of chemokines in response to TLR4 stimulation. 21 However, TLR4 has been localized to the glomerular endothelium rather than podocytes in frozen rat kidney, 24 and it seems likely that the findings would be the same in mice. Both Myd88 and TRIF dependent TLR4 signaling has been shown in murine mesangial cells, although TRIF deficient mice developed nephrotoxic nephritis to a similar degree to wild-type mice.…”
Section: Discussionmentioning
confidence: 99%
“…Concentration of TLR4 to the apical surface has been reported in a human colon cancer cell line (T84), murine colon crypts, inflamed colonic epithelia, rat kidney tubules, and gastric epithelium. [13][14][15][16] In the amnion, TLR4 does not localize to the apical membrane until the second trimester. This developmental change is similar to that observed in IEC, in that cellular differentiation is associated with a shift from cytoplasmic to apical TLR4 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, modulation of uroepithelial inflammation may be mediated by sensitization of the uroepithelium through regulation of epithelial TLR expression in response to infection or injury. An increase in TLR4 expression in the urinary epithelium has been observed during systemic sepsis in a murine model of cecal ligation and puncture (111), and an increase in renal epithelial TLR2 and TLR4 expression has been observed in a murine model of local renal inflammation induced by ischemia (112). Further demonstrating a role for TLR activation in uroepithelial inflammation, TLR4 mutant C3H/Hej mice failed to clear uropathogenic E. coli (UPEC) and showed reduced inflammatory mediator production compared with wild-type controls (109).…”
Section: Tlr-dependent Signaling In the Uroepithelial Tract: A Role Imentioning
confidence: 99%